2019
DOI: 10.1007/s11302-019-09672-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vascular smooth muscle cell calcification by ATP analogues

Abstract: Arterial medial calcification (AMC) has been associated with phenotypic changes in vascular smooth muscle cells (VSMCs) that reportedly makes them more osteoblast-like. Previous work has shown that ATP/UTP can inhibit AMC directly via P2 receptors and indirectly by NPP1-mediated hydrolysis to produce the mineralisation inhibitor, pyrophosphate (PP i). This study investigated the role of P2X receptors in the inhibitory effects of extracellular nucleotides on VSMC calcification. We found that Bz-ATP, α,β-meATP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Alternatively, we have treated both murine and human primary AML cells with different doses of ATP in vitro and revealed that the low dose of ATP (10-100 uM) indeed could enhance the proliferation of leukemia cells of WT, but not P2x7-KO, murine leukemia cells ( Figures S9A-S9B) or human ones ( Figures S9C-S9E). In contrast, the high dose of ATP (1 mM) inhibited leukemia cell growth ( Figures S9A-S9E), which might be resulted from nonspecific cytotoxicity (53)(54)(55). However, the apoptosis ( Figures S9F-S9J) and cell cycle ( Figures S9K-S9O) were not altered upon the treatment of low dose of ATP (the changes in high dose group may be due to nonspecific cytotoxicity), indicating that ATP mediated signaling may mainly sustain the self-renewal ability of leukemia cells and the blockade of the ATP-P2X7 pathway will be a potential strategy for the leukemia treatment.…”
Section: Targeting Aml Development By Suppressing Atp-p2x7 Signalingmentioning
confidence: 98%
“…Alternatively, we have treated both murine and human primary AML cells with different doses of ATP in vitro and revealed that the low dose of ATP (10-100 uM) indeed could enhance the proliferation of leukemia cells of WT, but not P2x7-KO, murine leukemia cells ( Figures S9A-S9B) or human ones ( Figures S9C-S9E). In contrast, the high dose of ATP (1 mM) inhibited leukemia cell growth ( Figures S9A-S9E), which might be resulted from nonspecific cytotoxicity (53)(54)(55). However, the apoptosis ( Figures S9F-S9J) and cell cycle ( Figures S9K-S9O) were not altered upon the treatment of low dose of ATP (the changes in high dose group may be due to nonspecific cytotoxicity), indicating that ATP mediated signaling may mainly sustain the self-renewal ability of leukemia cells and the blockade of the ATP-P2X7 pathway will be a potential strategy for the leukemia treatment.…”
Section: Targeting Aml Development By Suppressing Atp-p2x7 Signalingmentioning
confidence: 98%
“…The P2X receptor is of interest to researchers in relation to blood vessel smooth muscle cells (VSMC) e.g. synthetic ATP analogues and P2X receptor agonists (Bz-ATP, α, β-meATP and β, γ-meATP) have been shown to inhibit VSMC calcification in vitro [43]. However, there is little information regarding the effect of P2RX1 on the patency of the blood vessel, so this requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…VSMCs were identified by negative platelet endothelial cell adhesion molecule1 (marker of endothelial cells) and vimentin (marker of fibroblasts), and positive α-smooth muscle actin (marker of VSMCs) expression. VSMCs from the 3rd to 5th passages were used in the present study ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…TRIzol ® reagent (Invitrogen; Thermo Fisher Scientific, Inc.) was used to isolate total RNA from VSMCs according to the manufacturer's instructions. mRNA levels of SOD , Ang II and Ang II type 1 receptor ( AT1R ) in the VSMCs were detected using RT-qPCR ( 15 ). Briefly, first-strand cDNAs were reverse-transcribed from 2 µg of total RNAs using M-MLV (Moloney Murine Leukemia Virus Reverse Transcriptase) with oligo ( dT ); as the primer) and Rain in 1X M-MLV buffer.…”
Section: Methodsmentioning
confidence: 99%